2016
DOI: 10.1007/s11695-016-2087-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bariatric Surgery on Serum Bile Acid Composition and Conjugation in a Diabetic Rat Model

Abstract: The preferentially elevated serum taurine-conjugated BAs were similar after different bariatric surgeries, and the enhanced conjugation of BAs in the liver might account for the changed serum BAs profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
7
22
0
Order By: Relevance
“…Furthermore, coprophagy causes recirculation of secondary BAs, which increases their systemic concentrations (Groen, Kunne, & Oude Elferink, ; Krief, Jamart, & Hladik, ) in minipig and chimpanzee. This is in agreement with previous reports, where lowest primary/secondary BA ratios were observed in rabbit (1.1‐fold; Kasbo et al, ) and pig (1.2‐fold;Spinelli et al, ; Tsai et al, ), while it was highest in mice (2.6–8.6‐fold; Chen et al, ; Han et al, ), rat (2.1–7‐fold; Aoki et al, ; Wu et al, ) and hamster (5.4‐fold; Kasbo et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, coprophagy causes recirculation of secondary BAs, which increases their systemic concentrations (Groen, Kunne, & Oude Elferink, ; Krief, Jamart, & Hladik, ) in minipig and chimpanzee. This is in agreement with previous reports, where lowest primary/secondary BA ratios were observed in rabbit (1.1‐fold; Kasbo et al, ) and pig (1.2‐fold;Spinelli et al, ; Tsai et al, ), while it was highest in mice (2.6–8.6‐fold; Chen et al, ; Han et al, ), rat (2.1–7‐fold; Aoki et al, ; Wu et al, ) and hamster (5.4‐fold; Kasbo et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…We observed major species differences in multiple aspects of the plasma BA profiles. Similar to previous data our results showed that the highest total concentrations of plasma BAs were observed in the rat and pig (Garcia‐Canaveras, et al, ; Gunness et al, ; Tsai, Zhong, Weng, Huang, & Hsieh, ; Wu et al, ) and that G‐amidation was predominant in human and pig (Han et al, ; Spinelli et al, ; Tsai et al, ), while T‐amidation was predominant in rat, mice and dog (Ando et al, ; Aoki et al, ; Chen et al, ; Han et al, ; Marschall et al, ; Washizu, Ishida, Washizu, Tomoda, & Kaneko, ; Washizu, Tomoda, & Kaneko, ; Wu et al, ). Furthermore, in line with previous data we found that the BA pool in plasma was primarily composed of di‐OH BAs in humans, while tri‐OH BAs were the main components in rat, mice and hamster (Table ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, the duodenal-jejunal bypass isolates the ‘bypass’ portion of RYGB in the absence of gastric restriction and has metabolic effects in obese and lean rodents (Habegger et al, 2014; Kindel et al, 2011; 2009; B. Li et al, 2013; Rubino and Marescaux, 2004; Wu et al, 2016; X. Zhang et al, 2015).…”
Section: Bile Acids and Obesitymentioning
confidence: 99%
“…For example, Wu et al . performed duodenal-jejunal bypass (DJB) and sleeve gastrectomy in diabetic rats and found that the expression of amino acid N-acyltransferase Baat was up-regulated with increased serum conjugated bile acid levels 28 . As such, further investigation is warranted to understand the dynamics of Baat expression following RYGB and how that impacts the levels of conjugated bile acids either after fasting or post-prandial states.…”
Section: Discussionmentioning
confidence: 99%